Constrained spherical deconvolution analysis of the limbic network in human, with emphasis on a direct cerebello-limbic pathway - Arrigo, Alessandro; Mormina, Enricomaria; Anastasi, Giuseppe Pio; Gaeta, Michele; Calamuneri, Alessandro; Quartarone, Angelo; De Salvo, Simona; Bruschetta, Daniele; Rizzo, Giuseppina; Trimarchi, Fabio; Milardi, Demetrio (Frontiers in Human Neuroscience, 2014)
The limbic system is part of an intricate network which is involved in several functions like memory and emotion. Traditionally the role of the cerebellum was considered mainly associated to motion control; however several evidences are raising about a role of the cerebellum in learning skills, emotions control, mnemonic and behavioral processes involving also connections with limbic system. In fifteen normal subjects we studied limbic connections by probabilistic Constrained Spherical Deconvolution (CSD) tractography. The main result of our work was to prove for the first time in human brain the existence of a direct cerebello-limbic pathway which was previously hypothesized but never demonstrated. We also extended our analysis to the other limbic connections including cingulate fasciculus, inferior longitudinal fasciculus, uncinated fasciculus, anterior thalamic connections and fornix. Although these pathways have been already described in the tractographic literature we provided reconstruction, quantitative analysis and FA right-left symmetry comparison using probabilistic CSD tractography that is known to provide a potential improvement compared to previously used Diffusion Tensor Imaging techniques. The demonstration of the existence of cerebello-limbic pathway could constitute an important step in the knowledge of the anatomic substrate of non-motor cerebellar functions. Finally the CSD statistical data about limbic connections in healthy subjects could be potentially useful in the diagnosis of pathological disorders damaging this system.